Self-efficacy and Locus of Control as Predictors of the Efficacy of a Lifestyle Modification Program for Patients with Pre-Diabetes. - Milburn, Joseph F.; Parker, Katelyn; Peper, Angela D. (My University, 2009)
Lifestyle interventions reduce diabetes risk in pre-diabetes people. Programs such as the Diabetes Prevention Program (DPP)1involve intensive teaching, coaching, and counseling to help individuals exercise, lose weight, and monitor their own behavior. One question we addressed was whether we could use DPP materials in a classroom setting to teach people at risk for Type II diabetes to modify their lifestyles and to lose weight. A second question we addressed was whether the success of instructional approaches to lifestyle change may hinge on personality variables known to influence people?s capacity to manage their own behavior.
Color poster with text and graph describing research conducted by Joseph F. Milburn, Katelyn Parker, and Angela D. Peper, advised by Allen H. Keniston.
Keywords: Diabetes--Prevention; Prediabetic state--Treatment; Diabetes--Psychological aspects; Health behavior--Psychological aspects; Self-efficacy; Locus of control; Posters